The emperor has no clothes: A reply to Ginoux and Jovanovic - Vincent Carret (Duke University, Center for the History of Political Economy (CHOPE), 2023)
In a letter to the editors of the Journal of the History of Economic Thought, Jean-Marc Ginoux and Franck Jovanovic claim that my work on Ragnar Frisch is 'useless' and has 'no merit' (p.8). I will gladly take this opportunity to explain my research on Ragnar Frisch and why it remains unscathed from their hand-waving. It remains unscathed because their very narrow criticism of my mathematical solution of Frisch's model has no grounding. But it is also unscathed because they do not even address the historiographical points I was making in my paper.
Keywords: 330